Comparison of the Effect of Oral Pregabalin with Intravenous Ketamine on Reducing Pain after Abdominal Hysterectomy: A Randomized Double-blind Clinical Trial Study - Negin Ghadami; Farzad Sarshivi; Arvin Barzanji; Bijan Nouri; Zahra Mohammadi (Babol University of Medical Sciences, 2021)
Background: The aim of this study was to compare the analgesic effects of pregabalin and ketamine on reducing pain after abdominal hysterectomy. Methods: In this double-blind clinical trial, one hundred forty ASA I and II patients of age range 30-60 years scheduled for abdominal hysterectomy undergoing general anesthesia in 2018, were randomly divided into 4 equal groups. Pregabalin group received 300 mg oral pregabalin, ketamine group received 0.3 mg/kg of intravenous ketamine, and pregabalin- ketamine group received the combination of the two-above medication, and placebo group received the placebo and saline. Patients were evaluated for pain intensity according to the visual analogue scale (VAS) at 2, 4, 6, 12, 18, and 24 hours after surgery. Also, the need for analgesic drugs and the frequency of repetitions were also recorded. Statistical analysis was performed using STATA, Version 14. A p- value less than 0.05 was considered statistically significant. Results: In the pregabalin and pregabalin-ketamine groups, pain in the first 6 hours after the end of operation was significantly less than the other two groups (p<0.05), but there was no significant difference between the 4 groups at 18 and 24 hours after surgery. The need for analgesic medications in the pregabalin group was lower than in other groups (p<0.05). Conclusion: The results of this study show that the administration of oral pregabalin with and without intravenous ketamine before abdominal hysterectomy can decrease postoperative pain and reduce the need for analgesia.